The Intonational Systems of English and Croatian: A Bitonal Generative Compositional Approach - Josipović, Višnja (Array, 1995)
This paper presents the results of a research aimed at providing a comparison of the English and Croatian intonational systems within the framework of the bitonal generative compositional approach. This is done by comparing the intonational phrases of the original English corpus with their Croatian translational equivalents. The Croatian translational equivalents have been digitalized and subjected to the same type of computer analysis as was originally employed by Pierrehumbert (1980) in establishing the bitonal model. Conclusions are reached about the similarities and differences between the inventories of intonational morphemes in the two languages.